Malawi Agriculture and Food Security Policy Processes Baseline Survey, 2015 - International Food Policy Research Institute (International Food Policy Research Institute, 2019)
Several initiatives in Malawi have sought to strengthen the processes through which the design and content of policies, strategies, and programs in the agriculture sector that affect the nation’s food security are established. A two-part study was done under the New Alliance Policy Acceleration Support: Malawi Project (NAPAS: Malawi) to assess the quality of these policy processes and the institutional framework through which they are conducted and how perceptions of their quality have changed over time. The study is based on a two-round survey of national stakeholders in Malawi on issues centered on agriculture or food security that was conducted in 2015 and 2017/18. This study contains data from the endline survey. The endline survey was conducted in late 2017 and early 2018. The 86 individuals who made up the analytical sample for the baseline survey were contacted again and asked to complete an online questionnaire that replicated three of the five modules from the baseline survey. In total 55 respondents, while the other 12 endline survey respondents were replacements for baseline survey respondents who no longer participate in agriculture and food security policy processes in Malawi. These replacements generally were the current holders of the institutional positions held by the earlier baseline survey respondents. The endline survey consists of three modules. Respondent details; influence of institution within policy processes Opinion on quality of agriculture and food security policy processes in Malawi Opinion on quality of institutional architecture for agriculture and food security policy processes in Malawi